IMPLEMENTATION OF BIOGAS EQUIPMENT USING ARDUINO MEGA 2560 WITH SENSOR MQ-4 - Arianto, Kevin Inal; Baqaruzi, Syamsyarief; Zoro, Reynaldo (Jurnal Chemurgy, 2023)
The biogas in the research that the authors do is a mixture of cow dung with 1: 2 water, where the biogas in this study is carried out by anaerobic fermentation or without air, a mixture of cow dung and water is put into the reactor and the fermentation process is carried out for 12 days to prove whether biogas In this study, gas will be stored in storage (biogas bag 1 and biogas bag 2. The research method used, namely conducting literature studies, exploration, determining equipment specifications, designing and implementing and testing. In designing this tool, it is able to produce gas from the biogas fermentation process, namely methane gas which can be detected by a functioning methane gas sensor. Where there is an increase in PPM testing between the first MQ-4 sensor from 5246.36 and the second MQ-4 sensor detected at 5667.23 PPM with the adjusted difference of 420.87 PPM, so the methane gas is tested with a stove and a lighter. The MQ-4 sensor measurement error results reached 5.63%. Keywords: Reaktor fixed dome, MQ-4, Gas Metana, Monitoring